Placental mesenchymal dysplasia and intrauterine fetal growth restriction with doppler velocimetry alterations - a case report - Tozatti, Paula Vendruscolo; Muller, Ana Lúcia Letti; Sanseverino, Maria Teresa Viero; Magalhães, Jose Antonio de Azevedo; Rivero, Raquel; Gus, Rejane (Clinical and Biomedical Research, 2014)
Placental mesenchymal dysplasia (PMD) is a rare placental abnormality. We report a case of PMD associated with intrauterine growth restriction (IUGR), which was diagnosed by an ultrasound scan during the second trimester of pregnancy. A 36-year-old primiparous woman with signs of placental chorioangioma was referred to our hospital at the 23th gestational week. An ultrasonography revealed a small-for-gestational-age fetus with a large multicystic placenta. A serial Doppler sonographic assessment of umbilical and uterine artery blood flow showed a compromised fetus. A female, small-for-gestational-age baby was delivered by c-section at 28 weeks, and PMD was histopathologically confirmed.